Desordens tireoideanas em pacientes portadores de Hepatite C - Santos, Sandra Regina Xavier (2009)
Alpha Interferon and Ribavirin are the drugs of choice for treating Hepatitis C, but may trigger thyroid disorders as a major complication. Several studies have shown a prevalence vary (1% to 35%) of this association influenced by geographical distribution, genetics and iodine intake of the population. The objective of this study was to analyze the thyroid disorders in carrying patients of Hepatitis C in treatment or not with alpha Interferon and Ribavirin. We evaluated the frequency and pattern of thyroid disorders in 25 patients with hepatitis C in treatment with alpha interferon and Ribavirin (G1), 62 patients with Hepatitis C without treatment (G2) and 82 patients without Hepatitis C (control group) measuring TSH, antiperoxidase antibodies (anti-TPO) and antitireoglobulina (ATG). The hypothyroidism was more frequent in the carrying patients of Hepatitis C in treatment (36%), while the frequency of thyroid antibodies was not different in the three studied groups respectively (12% in G1; 8,06% in G2 and 17,07% in control group). It was not possible to demonstrate the biggest prevalence of Autoimmune Thyroid Disease in carrying patients of Hepatitis C in treatment with alpha Interferon and Ribavirin; even so the hypothyroidism has been more frequent in this group. Thus, carrying patients of Hepatitis C submitted to this treatment must make tracking of the thyroid dysfunction, as already considered for some authors.